One model to rule them all, one model to bind them? A critique of the use of accessibility-related models in post-secondary education. (2nd January 2022) - Seale, Jane; Burgstahler, Sheryl; Havel, Alice
ABSTRACT: The focus of this paper is to examine the role that models play in informing the approach that post-secondary education institutions take to developing inclusive and equitable practices that successfully and appropriately address the access needs of disabled students in relation to information and communications technology. It reviews the current approach of the post-secondary education community to using models to inform their accessibility practice with respect to ICT and explores the answers to three related questions: 1. What alternatives to the Universal Design model exist? 2. How do we differentiate between different accessibility models? 3. Do we need more than one model to inform accessibility practice? One key outcome of this exploration is a proposed evaluation framework that can help post-secondary institutions make informed decisions about the most appropriate model for them to adopt. The paper concludes that such a framework has potential to transform practitioners' approaches to accessibility by suggesting that excellence may not require a 'blanket approach' in which just one model 'rules' or dominates their thinking.